ADVOKASI GREENPEACE DALAM MENDESAK PENGHENTIAN PENGGUNAAN BATU BARA SEBAGAI SUMBER ENERGI PEMBANGKIT LISTRIK DI INDONESIA - Wulandari, Ni Komang Triani; Priadarsini, Ni Wayan Rainy; Parameswari, A.A.Ayu Intan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2019)
ABSTRACT Greenpeace as an international non-governmental organization committed to the environmental protection. This study aims Greenpeace’s advocacy in urging Indonesian Government to stop using coal as an energy source for electricity generation in Indonesia, in the periods of 2015 - 2017. This research used descriptive qualitative research methods by using the concept of NGOs and strategy and tactic of NGOs. Both of those concepts were able to explain the activity of Greenpeace as a advocacy NGOs in addressing environmental damage due to Indonesian Government policy. This study found that the advocacy of Greenpeace success in influencing the society of danger of coal in Indonesia.   Keyword: NGOs, Greenpeace Advocacy, Coal, Indonesia